A Phenomenological Perspective on Transformational Leadership Style and Work Motivation of Soldiers at Korem 101/Antasari - Ari Aryanto; Ahmad Alim Bachri; Anisah, Hastin Umi (Enigma in Economics, 2023)
This study aims to get a clear picture of the application of the transformational leadership style at Korem Antasari. This study seeks to explore the phenomenon of transformational leadership style and to find out and analyze whether the application of transformational leadership style has an effect on the work motivation of TNI AD soldiers at Korem 101/Antasari. Data for this study was collected from100 key informants whose willingness was based on snowball sampling and by observing as passive participants, semi-structured interviews, and with the help of open and closed question instruments. This research prioritized the emic perspective - with full attention to key informant perceptions. Miles and Huberman's phenomenological approach was used in this study. It was found that transformational leadership style has an effect on the work motivation of TNI AD soldiers at Makorem 101/Antasari.